2015
DOI: 10.20307/nps.2015.21.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Salternamide E from a Saltern-derived Marine ActinomyceteStreptomycessp.

Abstract: − Comprehensive chemical analysis of extracts and fractions of marine actinomycete strains led to the discovery of a new minor secondary metabolite, salternamide E (1), from a saltern-derived halophilic Streptomyces strain. The planar structure of salternamide E (1) was elucidated by a combinational analysis of spectroscopic data including NMR, MS, UV, and IR. The absolute configuration of salternamide E (1) was determined by circular dichroism spectroscopic analysis. Salternamide E displayed weak cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Compound 2 (10 mg) was purified from subfraction H54 (120 mg) by semi-preparative normal-phase HPLC (Apollo Silica column, 250×10.0 mm, 5 µm, flow rate: 2 mL/min) with an isocratic solvent system of CHCl 3 Cytotoxicity Assay A sulforhodamine B (SRB) bioassay was used to determine the cytotoxicity of each isolated compound against four cultured human tumor cell lines. [21][22][23][24][25][26] The cell lines used were A549, SK-OV-3, SK-MEL-2, and HCT-15. Doxorubicin was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Compound 2 (10 mg) was purified from subfraction H54 (120 mg) by semi-preparative normal-phase HPLC (Apollo Silica column, 250×10.0 mm, 5 µm, flow rate: 2 mL/min) with an isocratic solvent system of CHCl 3 Cytotoxicity Assay A sulforhodamine B (SRB) bioassay was used to determine the cytotoxicity of each isolated compound against four cultured human tumor cell lines. [21][22][23][24][25][26] The cell lines used were A549, SK-OV-3, SK-MEL-2, and HCT-15. Doxorubicin was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…However, the chemistry of actinobacteria in these hypersaline environments had been mostly neglected until our report of the salternamides as the first secondary metabolites from a saltern-derived actinomycete ( Streptomyces sp.) in 2015 [ 5 , 6 ]. A subsequent biological study of salternamide A revealed that this chlorinated metabolite suppresses the hypoxia-induced accumulation of HIF-1 α and induces apoptosis in human cancer cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As part of our efforts to discover new bioactive natural products, we have been investigating the chemistry of actinobacteria derived from marine and saline environments including salterns [5,6,7], intertidal zones [8,9,10,11], and deep-sea sediments [12]. In our previous reports, novel bioactive secondary metabolites were mainly identified through the chemical profiling of bacterial secondary metabolites by LC/MS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the importance of using combinations of chemical and computational analyses, it is critical to focus on prolific sources of structurally and biologically novel compounds because of the constant clinical need for new chemical entities with pharmaceutical potential [ 4 ]. As part of our efforts to discover new bioactive natural products, we have been investigating the chemistry of actinobacteria derived from marine and saline environments including salterns [ 5 , 6 , 7 ], intertidal zones [ 8 , 9 , 10 , 11 ], and deep-sea sediments [ 12 ]. In our previous reports, novel bioactive secondary metabolites were mainly identified through the chemical profiling of bacterial secondary metabolites by LC/MS analysis.…”
Section: Introductionmentioning
confidence: 99%